(untitled) (gjstudies, 2022)
This study investigates the complex relationship between audit pricing structuresand the actual effort levels exerted by audit firms, challenging the traditional assumption that higher fees necessarily correlate with greater audit effort. We introduce anovel methodological framework that combines econometric analysis with behavioralaudit simulations to disentangle the components of audit pricing—risk premiums, effort compensation, and client-specific premiums—from observable effort metrics. Unlike prior research that relies on fee data as a proxy for effort, we develop and validatea multi-dimensional effort measurement instrument capturing planning hours, testingintensity, review layers, and professional skepticism application. Our analysis of aunique dataset spanning 450 audit engagements from 1998 to 2004 reveals three distinct pricing-effort relationships: (1) a positive but diminishing correlation in high-riskengagements where effort responds to risk-based pricing, (2) a neutral relationshipin moderate-risk engagements where standardized pricing dominates, and (3) a negative relationship in low-risk, recurring engagements where fee stickiness coexists witheffort reduction. We further identify a previously undocumented ’effort elasticity’ phenomenon, where audit effort demonstrates varying sensitivity to fee changes dependingon client tenure, auditor size, and regulatory environment. The findings challenge conventional audit pricing models and provide new insights for regulators concerned withaudit quality indicators, audit firms designing compensation structures, and clientsnegotiating audit engagements. This research contributes to the audit literature byproviding a more nuanced understanding of how pricing mechanisms actually influenceauditor behavior, moving beyond simple input-output models to recognize the complexbehavioral and economic interdependencies in audit production.